Seasonal small mammal diversity, endocrine correlates, and diet behaviour in rodents across transformed and pristine ecosystems in the Magaliesberg - Ganswindt, Andre (University of Pretoria, 2025)
Thesis (PhD (Zoology))--University of Pretoria, 2025.